Severe Congenital Toxoplasmosis: A Case Report and Strain Characterization - Bahador Sarkari (Case Reports in Infectious Diseases, 2015)
We report a fatal congenital toxoplasmosis case in an Iranian woman in the south of Iran. A pregnant mother had been admitted at the 15th week of her pregnancy on account of a febrile illness, symptoms of common cold, and enlargement of submandibular lymph nodes. Serological testing of the mother’s serum revealed positive IgG and IgM anti-Toxoplasma antibodies. Amniotic fluid was taken and evaluated by polymerase chain reaction (PCR) assay with a direct amplification of the Toxoplasma URPT gene which was found to be positive. Sequencing and analysis of PCR product revealed that the isolate has the most similarity with type I of Toxoplasma gondii. Fetal scan showed anomaly in fetus including mild hydrocephaly. Termination of the pregnancy was suggested by the physician and pregnancy was terminated 178 days after conception.